The Vanderbeekers Make a Wish - Book 5 - Glaser, Karina Yan (Boston ; Houghton Mifflin Harcourt, 2021)
One hilarious Harlem family is on a mission to find the perfect way to celebrate their Papa's fortieth birthday while discovering more about their mysterious grandparents in this heartfelt romp and latest installment to the New York Times best-selling series, perfect for fans of the Penderwicks. It's summer on 141st Street, and the Vanderbeekers are looking forward to Papa's surprise fortieth birthday party. But then Papa must leave town to help his best friend and the Vanderbeeker children are surprised to find their maternal grandparents on their doorstep. Grandma is very critical of everything they do. Meanwhile, they find themselves learning more about their papa's father than ever before, and wishing they could have known him a bit better. Can they learn more about the grandfather they lost and come to appreciate the grandparents they still have while making sure their papa has the best birthday ever?
Keywords: Families -- Juvenile fiction; Mixed families -- Juvenile fiction; Neighbors -- Juvenile fiction; Friendship -- Juvenile fiction; Birthday parties -- Juvenile fiction; Grandparents -- Juvenile fiction; Racially mixed children -- Juvenile fiction; Family life -- Fiction. -- New York (State); Racially mixed families -- Fiction; Friendship -- Fiction; JUVENILE FICTION / Family / Multigenerational; JUVENILE FICTION / Family / Parents; JUVENILE FICTION / Holidays & Celebrations / Birthdays; JUVENILE FICTION / Family / General (see also headings under Social Themes).; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / General; African Americans; Birthday parties; Families; Friendship; Grandparents; Neighbors; Racially mixed children; Racially mixed families; Family -- Juvenile fiction; African Americans -- Juvenile fiction; Friendship -- Juvenile fiction; Harlem (New York, N.Y.) -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Family life -- Fiction; African Americans -- Fiction; Friendship -- Fiction; Harlem (New York, N.Y.) -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Harlem (New York, N.Y.) -- Fiction; New York (N.Y.) -- Fiction; New York (State) -- New York; New York (State) -- New York; Harlem (New York, N.Y.) -- Fiction; New York (N.Y.) -- Fiction; Juvenile Fiction; Fiction; Juvenile works; Fiction